ANALISIS KESIAPAN GURU DALAM PENDEKATAN DEEP LEARNING DI SD BABUSSALAM PEKANBARU - Ilhami Zahra Shofa; Zetra Hainul Putra; Intan Kartika Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Within the Merdeka Curriculum, there is an emphasis on the deep learning approach. Elementary school teachers must be prepared for deep learning because it enables them to select and apply educational applications that are not only entertaining but also support deep conceptual understanding rather than mere memorization. This study aims to describe the readiness of elementary school teachers toward the deep learning approach at SD Babussalam Pekanbaru. The study employs a qualitative approach with a descriptive qualitative method. Data collection techniques include observation, interviews, and documentation. The results indicate that the readiness of teachers at SD Babussalam regarding the concept of deep learning is still at an early and limited stage. Although the teachers demonstrate strong self-confidence and a positive attitude toward the potential of deep learning to improve the quality of instruction, they require structured formal training to gain a better understanding of deep learning.